2010
DOI: 10.4049/jimmunol.0903712
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum Aminopeptidase Associated with Antigen Processing Defines the Composition and Structure of MHC Class I Peptide Repertoire in Normal and Virus-Infected Cells

Abstract: The MHC class I (MHC-I) molecules ferry a cargo of peptides to the cell surface as potential ligands for CD8+ cytotoxic T cells. For nearly 20 years, the cargo has been described as a collection of short 8-9 mer peptides, whose length and sequences were believed to be primarily determined by the peptide-binding groove of MHC-I molecules. Yet the mechanisms for producing peptides of such optimal length and composition have remained unclear. In this study, using mass spectrometry, we determined the amino acid se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
62
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 82 publications
(70 citation statements)
references
References 43 publications
6
62
1
1
Order By: Relevance
“…Interestingly, although ERAP1 trims peptides from the N-terminus, these longer peptides found were predominantly C-terminally extended. This is in apparent contrast to the findings from studies performed in mice, where extended class I MHC peptides caused by ERAAP knockout were found to be mainly N-terminal extensions (13). The likely explanation, supported by our in vitro binding studies, is that N-terminally extended epitopes lacking Arg-2, which is critical for the HLA-B27 binding motif, bind so poorly to HLA-B27 that they are rarely detected.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Interestingly, although ERAP1 trims peptides from the N-terminus, these longer peptides found were predominantly C-terminally extended. This is in apparent contrast to the findings from studies performed in mice, where extended class I MHC peptides caused by ERAAP knockout were found to be mainly N-terminal extensions (13). The likely explanation, supported by our in vitro binding studies, is that N-terminally extended epitopes lacking Arg-2, which is critical for the HLA-B27 binding motif, bind so poorly to HLA-B27 that they are rarely detected.…”
Section: Discussioncontrasting
confidence: 99%
“…Our finding that ERAP1 silencing increases the proportion of longer peptides (11-13 mer) bound to HLA-B27 is consistent with previous data on murine class I MHC (13). We also found that ERAP1 silencing changed the nature of the P1 amino acid of peptides bound to HLA-B27, increasing the abundance of uncharged polar residues (S, Y, and T) while reducing the prevalence of E and R residues.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…5). This pattern is similar to that observed in cells where peptide loading is obstructed by tapasin deficiency or where peptide trimming is reduced by inactivation of endoplasmic reticulum aminopeptidase associated with antigen processing (ERAAP) (31,32). These observations hint at temperature-dependent conformational adaptations in the H-2K b peptide-binding groove, following the initial binding event.…”
Section: Discussionsupporting
confidence: 65%
“…The composition of the peptide-MHC class I repertoire is determined primarily by peptide-binding properties of MHC class I itself, but tapasin and ERAAP further shape the peptide repertoire presented (Fig. 5) (31,32). Of note, Duan et al (35) showed that cancer neopeptides that elicit CD8+ T-cell immunity may reflect the peptide pool detected at 26°C and then expand the MHC class I-associated peptidome considered by the immune system.…”
Section: Discussionmentioning
confidence: 99%